RELIGIOUS AND PSYCHOLOGICAL FEATURES OF DECISION-MAKING - Садыкова Гульбарно (Journals Park Publishing, 2024)
In this article, the religious and psychological features of decision-making were studied and the corresponding conclusions were made.
Keywords: decision-making, religious-psychological feature, yoga, religious orientation.